2020
DOI: 10.2196/18513
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Apps for Medical Emergencies: Systematic Review

Abstract: Background Mobile health apps are used to improve the quality of health care. These apps are changing the current scenario in health care, and their numbers are increasing. Objective We wanted to perform an analysis of the current status of mobile health technologies and apps for medical emergencies. We aimed to synthesize the existing body of knowledge to provide relevant insights for this topic. Moreover, we wanted to identify common threads and gaps … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
0
21
0
2
Order By: Relevance
“…Only 5 diagnostic apps were evaluated. It is worth mentioning STB—Stop The Bleed , an app designed to help anyone learn how to safely and effectively deal with life-threatening bleeding, which has demonstrated the potential of mobile apps in emergency scenarios [ 30 ]. The other 4 diagnostic apps are screening tools based on hematological parameters, questionnaires, and gene traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 5 diagnostic apps were evaluated. It is worth mentioning STB—Stop The Bleed , an app designed to help anyone learn how to safely and effectively deal with life-threatening bleeding, which has demonstrated the potential of mobile apps in emergency scenarios [ 30 ]. The other 4 diagnostic apps are screening tools based on hematological parameters, questionnaires, and gene traits.…”
Section: Discussionmentioning
confidence: 99%
“…Patients usually search for a health app that allows for medication management, clinical and analytical parameter register, and symptom tracking [ 28 , 37 ]. Patients with hematological conditions would benefit significantly from this type of assistance, as several blood conditions demand constant patient monitoring and high adherence to treatment for a better health outcome [ 18 , 30 ]. My INR , INR Care , and Diario de INR are apps that allow anticoagulated patients to record and track their international normalized ratio readings and antivitamin K dosages.…”
Section: Discussionmentioning
confidence: 99%
“…Supported by the rapid spread of mobile devices and their innovative features (eg, connectivity, embedded computing capabilities, small size, and versatility), mobile health (mHealth) apps have great potential as tools to support out-of-hospital emergency drug preparation at the point of care. However, a recent systematic review showed that few mHealth apps are available for prehospital settings [ 35 ]. Among these mHealth apps, none has been validated to specifically support emergency drug preparation by EMS personnel with the aim of reducing medication dosing errors and the stress hassle of this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Kerst, Zielasek e Gaebel, 2020), principalmente entre profissionais jovens (Plaza Roncero et al, 2020).…”
Section: Aplicabilidade Do Protocolo Na Prática Clínicaunclassified
“…Além disso, apenas 45,8% dos médicos residentes de psiquiatria consideram a plataforma REDCap de fácil entendimento. Esse dado foi surpreendente, uma vez que dados da literatura sugerem que os dispositivos móveis como aplicativos estão se tornando os principais instrumentos de acesso à informação clínica, especialmente para estudantes e jovens profissionais de saúde (Plaza Roncero et al, 2020). Em geral, o uso do REDCap é considerado de fácil entendimento, sendo esse método preferido ao uso de papel e caneta (Grimes et al, 2020;Thomas et al, 2020), mesmo em população idosa (Hurria et al, 2016).…”
Section: Aplicabilidade Do Protocolo Na Prática Clínicaunclassified